Pendidikan Rabbani dalam Keluarga Perspektif Sayyid Muhammad Bin Alawi Al-Maliki - Huda, Khoirul (EDU-RELIGIA : Jurnal Keagamaan dan Pembelajarannya, 2024)
This study examines the concept of robbani education in the family from the perspective of Sayyid Muhammad Bin Alawi Al-Maliki and how to apply the concept of robbani education in Islamic families. By using library research, the primary data sources are Adabul Islam fi nidzom al-usroh and the book At-tahliyah wa at-targhib fi at-tarbiyah wa at-tahdzib. The results of the analysis show that rabbani education from the perspective of Sayyid Muhammad bin Alawi Al-Maliki can be achieved with the following indicators; 1) Aqidah/Faith; 2) Morals; 3) Knowledge; 4) Leadership; 5) Social community; 6) Indicator of Keeping Secrets; 7) Nationalism; 8) Deliberation/democracy; 9) Discipline